2008
DOI: 10.1159/000168676
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone, a Peroxisome Proliferator-Activated Receptor Gamma Ligand, Suppresses Bleomycin-Induced Acute Lung Injury and Fibrosis

Abstract: Background: Peroxisome proliferator-activated receptor-γ (PPARγ) ligands have been shown to possess potent anti-inflammatory actions. Idiopathic interstitial pneumonia is defined as a specific form of chronic fibrosing lung disease characterized by progressive fibrosis which leads to deterioration and destruction of the lungs. Objective: To investigate whether the PPARγ ligand pioglitazone (PGZ) inhibited bleomycin (BLM)-induced acute lung injury and subsequent fibrosis. Methods: BLM was administered intratrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(62 citation statements)
references
References 73 publications
1
61
0
Order By: Relevance
“…Consequently, PPAR-a and PPAR-c agonists may be helpful in the treatment of acute inflammatory diseases, such as ALI [13]. In this context, several studies have proven a beneficial role for PPAR-c agonists in models of allergic airway inflammation and bleomycin-induced ALI [14,15].…”
mentioning
confidence: 99%
“…Consequently, PPAR-a and PPAR-c agonists may be helpful in the treatment of acute inflammatory diseases, such as ALI [13]. In this context, several studies have proven a beneficial role for PPAR-c agonists in models of allergic airway inflammation and bleomycin-induced ALI [14,15].…”
mentioning
confidence: 99%
“…PPAR␥ ligands, such as the thiazolidinedione (TZD) class of anti-diabetic drugs (e.g. pioglitazone, rosiglitazone, ciglitazone, and troglitazone), inhibit the expression of various inflammatory proteins like inducible nitric-oxide synthase, tumor necrosis factor-␣ (TNF␣), and matrix metallopeptidase (MMP9) in macrophages (37) and suppress the fibrosis of lung fibroblasts (35,38,39), dermal fibroblasts (40), and retinal pigment epithelial cells (41). The mechanism of action of PPAR␥ ligands is under investigation but involves both PPAR␥-dependent and PPAR␥-independent pathways (35).…”
mentioning
confidence: 99%
“…Pulmonary fibrosis and impaired lung function are the most serious complications of bleomycin treatment. In vivo studies showed that both natural and synthetic PPAR-g agonists suppressed bleomycininduced lung injury and fibrosis (43), and also inhibited inflammation, as well as skin and lung fibrosis in a murine model of scleroderma (44).…”
Section: Discussionmentioning
confidence: 99%